Ecstasy - Irvine Welsh (London Vintage, 1997)
With three delightful tales of love and its ups and downs, the ever-surprising Irvine Welsh virtually invents a new genre of fiction: the chemical romance . In "Lorraine Goes to Livingston," a bestselling authoress of Regency romances, paralyzed and bedridden, plans her revenge on gambling, whoring husband with the aid of her nurse Lorraine. In "Fortune's Always Hiding," flawed beauty Samantha Worthington enlists a smitten young soccer thug to find the man who marketed the drug that crippled her from birth-in order to give his a taste of his own disastrous medicine. In the upbeat final tale "The Undefeated," we experience the transfiguring passion of the miserably married young yuppie Heather and the raver Lloyd from Leith-a grand affair played out to a house music beat. As these fools for love pursue it in all the wrong places, Ecstasy is guaranteed to set pulses racing and hearts aflutter.
Keywords: Fiction; Short Stories